The Right to use Land in China: an Instrument of Economic Development? (TEST Trento Student Law Review, 2023)
This article aims to give an in-depth review of land use rights in China, comparing the similarities and differences between land use rights in China and in the Western World, with an eye specifically on Italy. From a historical perspective, we will try to understand how the entire system evolved to the point in which it is today.We will discuss land leasing as a form for cities and local governments to have a steady source of revenue genuinely within their control and the process of land conversion. We will analyze how the land use system became a sort of zoning arrangement for China. We will see what is the role of the courts in this delicate system, that balances socialist ideals and capitalistic needs, through some decisions on different aspects of the right to use land.We will try, even though it is most surely impossible, to give a complete analysis of the matter through the lenses of the comparative jurist. We will touch on some economic and financial aspects of the land use right.
Keywords: China; private law; Right to use land; Right of property; Legal comparison